Middle and Upper Palaeolithic environments and the calibration of 14C dates beyond 10,000 BP - Andel, Tieerd H. van
Advances in our understanding of the Quaternary history of the earth's magnetic field provide the means to correct the radiocarbon time-scale for long-term (millennia) deviations from the calendrical one beyond the upper limit of the tree-ring-based calibration. The conversion is essential when Middle and Upper Palaeolithic archaeological sites are to be placed within the context of the complex climatic history of the last glacial interval and following deglaciation.